Navigating Dual-Structured Crisis: Factors Influencing Nonprofit Organizational Resilience - Vien, Ha B.; Hoang, Thanh Thi (Nonprofit and Voluntary Sector Quarterly, 2026)
The COVID-19 pandemic constituted an unprecedented exogenous shock to many nonprofit organizations, testing their ability to sustain operations and adapt to crises. Building on population ecology and nonprofit organizational resilience framework, this study conceptualizes COVID-19 as a dual-structured crisis and examines how organizational factors, coupled with resilience tactics, shape nonprofit resilience. Results from 169 nonprofits highlight that specialist organizations (art and culture) are more vulnerable to external crisis than generalist nonprofits (human services). While donor support was critical for sustaining human-service organizations, peer support from other nonprofits emerged as a key factor for arts and culture organizations. In addition, system-wide constraints muted the effects of traditional strategies such as technology adoption and federal funding access on nonprofit resilience. Our findings underscore the context-dependent effectiveness of resilience tactics and offer new insights into managing nonprofits in future crises.
Keywords: dept.pch